Leonid Andreev’s Metaprose: Poetics and Conceptual Basis - Московкіна, Ірина Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article proposes a typology of metatexts by Leonid Andreev, summarizes the study of his feuilletons, letters, diaries and fiction of the 1890-1900s. With this in mind, the specifics of the poetics and the conceptual basis of the metatexts of the writer of the 1910s - Letters About the Theater in the context of his dramas, “panpsychic dramas”, “one-act little comedies”, short stories of the 1910s and the final myth novel The Diary of Satan are characterized. An important genre-forming and conceptual role of artistic imagery in the Letters on the Theater (intertextuality, metaphors, irony, paradox, etc.), characteristic of his prose and dramaturgy of this period, is shown. It is revealed that the metaphors in Letters on the Theater sought to fulfill the functions of concepts, but being artistic images at the same time, they were characterized by semantic ambiguity, which created an opportunity for different interpretations of what was said. Therefore, the interpretation of the “panpsychic “panpsychic theory in the Letters on the Theater is still ambiguous. In turn, the artworks of the writer of the 1910s were characterized by metatextuality. Andreev’s ironic short stories (Donkeys, Herman and Martha, Cuckolds, Suitcases, etc.), his “one-act little comedies” (Love for the Neighbor, Honor (The Old Count), Beautiful Sabine Women, Horse in the Senate, Monument, etc.) and the myth-novel Satan’s Diary are characterized as meta-text, which reflected Andreev’s views on the “old”, Shakespearean, and “new” drama, debates about the creation of which were conducted at the beginning of the twentieth century . In the dramas of the 1910s (Ekaterina Ivanovna, Thought, Samson in Shackles, Requiem, etc.), the theory of the “panpsychic” theater was tested, and concrete forms of the embodiment of the conflict not generated by primary passions (hunger, love, ambition, etc.), but by human thought in its suffering, joy and struggle, were sought.